A method, index and system for evaluating the quality of a granitic pegmatite type high-purity quartz raw material
Patent Information
- Application Number
- CN202611160967.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]花岗伟晶岩是我国分布最广、储量最大的高纯石英原料矿,由于其地质成因情况复杂,导致各地区矿的杂质赋存情况大相径庭,同时影响高纯石英最终纯度的因素有多方面,但目前国内尚无统一标准来对原料进行评估
[0032]与现有技术相比,本发明的有益效果包括以下内容中的至少一项:
Smart Images

Figure CN123017233A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-purity quartz sand materials, and more specifically, to a quality evaluation method, rating index, and system for granite pegmatite-type high-purity quartz raw materials. Background Technology
[0002] High-purity quartz is a mineral product obtained by refining ores such as crystal, vein quartz, and granite pegmatite. It is the material basis for high-end products in the silicon industry, possessing excellent physicochemical properties such as high temperature resistance, corrosion resistance, low thermal expansion, high insulation, and high light transmittance. It is widely used in semiconductors, photovoltaics, fiber optic communication, optics, and electric light sources, and is a key basic material for strategic emerging industries such as next-generation information technology, new energy, and high-end equipment. Although my country's high-purity quartz production has increased year by year, my country is currently the world's largest importer of high-purity quartz industrial raw materials, relying mainly on imports from the United States for high-end, high-purity quartz. Therefore, research on the development and utilization of high-purity quartz raw materials in China is urgently needed to break through international technological blockades and achieve domestic self-sufficiency in high-purity quartz and downstream industries. Currently, my country has not yet fully mastered the core technology for purifying high-purity quartz sand from natural rock minerals. Finding suitable quartz raw materials and conducting targeted purification research is of great significance.
[0003] Granite pegmatite is the most widely distributed and largest-reserved high-purity quartz raw material mine in my country. Due to its complex geological formation, the impurity content varies greatly from region to region. Furthermore, many factors influence the final purity of high-purity quartz, but currently there is no unified standard in China to evaluate the raw materials. Therefore, establishing an evaluation system specifically for high-purity quartz from granite pegmatite is of significant practical importance for optimizing the development and utilization of high-purity quartz resources and helping enterprises reduce costs and improve product quality. Summary of the Invention
[0004] The purpose of this invention is to address at least one of the aforementioned deficiencies in the prior art. For example, one objective of this invention is to provide a method for evaluating the quality of high-purity quartz raw materials of granite pegmatite type; a second objective of this invention is to provide a quality rating index for high-purity quartz raw materials of granite pegmatite type; and a third objective of this invention is to provide a quality rating system for high-purity quartz raw materials of granite pegmatite type.
[0005] To achieve the above objectives, the present invention provides a method for evaluating the quality of high-purity quartz raw materials of granite pegmatite type, the evaluation method comprising: 1) Analyze the mineral composition of the raw ore to obtain a mineral composition rating; 2) Analyze the weathering degree of the raw ore to obtain a weathering degree rating for the raw ore; 3) Analyze the mineral distribution pattern of the raw ore to obtain a mineral distribution pattern rating. 4) Perform physical separation on the raw ore and analyze the morphological characteristics of the physical separation concentrate to obtain a morphological characteristic rating of the physical separation concentrate; 5) Analyze the SiO2 content of the physical beneficiation concentrate to obtain the SiO2 content rating of the physical beneficiation concentrate; 6) Perform chemical separation on the physically separated concentrate, and analyze the SiO2 content of the chemically separated concentrate to obtain the SiO2 content rating of the chemically separated concentrate; 7) Summarize the rating results from steps 1)-6) to complete the quality evaluation of granite pegmatite-type high-purity quartz raw materials.
[0006] Optionally, the mineral composition rating of the raw ore includes four levels: a, b, c, and d. The primary gangue mineral in the grade a raw ore is muscovite, with a small amount of feldspar. The primary gangue mineral in the grade b raw ore is feldspar, with a small amount of muscovite or biotite. The grade c raw ore contains more than 5% of three or more gangue minerals, including feldspar, muscovite, biotite, tourmaline, and rutile. The grade d raw ore contains more than 5% of four or more gangue minerals, including feldspar, muscovite, biotite, tourmaline, rutile, anatase, and clay minerals. The feldspars include potassium feldspar, sodium feldspar, and calcium feldspar, as well as their isomorphous series products.
[0007] Optionally, the weathering degree rating of the raw ore includes four levels: a, b, c, and d. The grade a raw ore has stable mineral crystallinity and no weathering traces. The grade b raw ore shows weathering on the surface and occasionally exhibits feldspar kaolinization characteristics. The grade c raw ore has a high degree of weathering, with clay minerals appearing in the crystal phase and the clay phase content exceeding 3%. The grade d raw ore is severely weathered and cannot maintain a blocky morphology, appearing as sandy or sandy ore particles.
[0008] Optionally, the mineral embedding status rating of the raw ore is based on the embedding characteristics between quartz and gangue minerals in granite pegmatite, including four levels: a, b, c, and d. In the a-level raw ore, the quartz exhibits wavy extinction, and the mineral embedding is mainly composed of independent associated minerals. In the b-level raw ore, the quartz grains are intact, and the embedded minerals are mainly muscovite and feldspar filling the intercrystalline fissures of quartz. In the c-level raw ore, there are many embedded minerals inside the quartz grains, and the embedding size is above the micrometer level. In the d-level raw ore, there are many columnar embedded minerals and needle-like micrometer / submicrometer-sized solid inclusions inside the quartz grains.
[0009] Optionally, the morphological characteristics rating of the physical beneficiation concentrate is based on the microscopic morphology of the concentrate obtained from the physical beneficiation of granite pegmatite, including four levels: a, b, c, and d. In level a physical beneficiation concentrate, the quartz grains are transparent and free of staining, with few solid inclusions inside the grains, and a small number of gas-liquid inclusions, mainly secondary / pseudo-secondary. In level b physical beneficiation concentrate, the quartz grains are transparent and have little surface staining, with few solid inclusions inside the grains, and a small number of gas-liquid inclusions. In level c physical beneficiation concentrate, the quartz grains show staining, occasionally with dark particles mixed in, and a large number of solid or gas-liquid inclusions inside the grains. In level d physical beneficiation concentrate, the quartz grains show staining, with dark particles mixed in, and a large number of complex types of gas-liquid inclusions inside the grains, showing characteristics of original gas-liquid inclusions.
[0010] Optionally, the SiO2 content rating of the physical beneficiation concentrate is based on the impurity content of the concentrate obtained from the physical beneficiation of granite pegmatite, including four levels: a, b, c, and d. The SiO2 chemical purity of the grade a physical beneficiation concentrate is greater than 99.95%; the purity of the grade b physical beneficiation concentrate is greater than 99.9%; the purity of the grade c physical beneficiation concentrate is greater than 98%; and the purity of the grade d physical beneficiation concentrate is less than 98%.
[0011] Optionally, the SiO2 content rating of the chemically beneficiated concentrate is based on the impurity content of the concentrate obtained from the chemical beneficiation of granite pegmatite, including four levels: a, b, c, and d. The grade a chemically beneficiated concentrate has a purity greater than 4N5 and the main chemical components of the impurities are K and Na. The grade b chemically beneficiated concentrate has a purity greater than 4N and the main chemical components of the impurities are Al, K, Na, Fe, and Mg. The grade c chemically beneficiated concentrate has a purity greater than 3N and the main chemical components of the impurities are Al, K, Na, Fe, Mg, Ca, and Ti. The grade d chemically beneficiated concentrate has a purity less than 3N and complex impurity chemical components, and is therefore rated as grade d.
[0012] Alternatively, the method for analyzing the mineral composition of the raw ore in step 1) includes determining the mineral composition and chemical composition of the granite pegmatite raw ore by X-ray diffraction combined with X-ray fluorescence spectroscopy.
[0013] Alternatively, step 2) can be used to analyze the weathering degree of the raw ore by sampling the appearance and morphological characteristics of the raw ore hand specimens.
[0014] Optionally, step 3) involves analyzing the mineral distribution of the raw ore, including observing granite pegmatite ore slices using a transmitted, reflected, and polarized light microscope to identify the distribution of gangue minerals and quartz, as well as the inclusion of impurities within the quartz.
[0015] Optionally, the analysis of the morphological characteristics of the physical separation concentrate includes observing quartz concentrate particles through a transmitted, reflected and polarized light microscope to identify the proportion of gangue minerals in the concentrate, the embedding characteristics of quartz inclusions, and the morphology and particle size of quartz particles.
[0016] Alternatively, the physical separation concentrate is prepared from granite pegmatite ore through one or more non-chemical methods, such as sand making, gravity separation, magnetic separation, flotation, color separation, and electrostatic separation.
[0017] Alternatively, the chemically separated concentrate is a highly purified quartz sand obtained by purifying the physically separated concentrate through high-temperature acid leaching, chlorination roasting, and hot-press acid leaching.
[0018] Alternatively, the analytical method for the SiO2 content includes detecting the trace element chemical composition in high-purity quartz by ICP-OES (inductively coupled plasma optical emission spectrometry) or ICP-MS (inductively coupled plasma mass spectrometry), and the SiO2 content is obtained by the difference method, i.e., w(SiO2) = (1 – w (杂质元素总量) ) × 100%.
[0019] In another aspect, the present invention provides a quality rating index for high-purity quartz raw materials of granite pegmatite type, which is applicable to the quality evaluation method of high-purity quartz raw materials of granite pegmatite type described above.
[0020] Optionally, the rating index includes six elements: A - mineral composition of the raw ore, B - weathering degree of the raw ore, C - mineral dissemination state of the raw ore, D - morphological characteristics of the physically separated concentrate, E - SiO2 content of the physically separated concentrate, and F - SiO2 content of the chemically separated concentrate. The rating of each of the six elements includes four levels: a, b, c, and d. The comprehensive rating result provides a quality evaluation of the granite pegmatite-type high-purity quartz raw material. Materials with at least three grades of A are classified as Grade 1 high-purity quartz raw materials; Materials with at least three grades of B or higher are classified as secondary high-purity quartz raw materials; Materials with at least two grades of B or higher are classified as Grade III high-purity quartz raw materials; It is recommended that fewer than two of grade B or higher be developed and utilized as non-high-purity quartz raw materials.
[0021] Alternatively, the primary high-purity quartz raw material can be purified to obtain high-purity quartz of grade 4N5 or higher after the purification process is optimized. The secondary high-purity quartz raw material can be used to prepare high-purity quartz of grade 4N or higher after the purification process is optimized. The three-level high-purity quartz raw materials can be used to prepare high-purity quartz of grade 3N or higher after the purification process is optimized.
[0022] In another aspect, the present invention provides a quality rating system for high-purity quartz raw materials of granite pegmatite type. The evaluation system can realize the quality evaluation method of granite pegmatite type quartz raw materials described above, and is based on the quality rating index of granite pegmatite type high-purity quartz raw materials described above.
[0023] Optionally, the rating system adopts a semi-quantitative threshold grading evaluation method, and the indicators for evaluating and grading six elements of granite pegmatite ore and its physical and chemical beneficiation concentrate are programmable through digital signal logic circuits; the rating system is a multi-index rating system composed of a decoder, a full adder, a carry-lookahead adder, a numerical comparator, and a counter.
[0024] Optionally, the rating system is configured with six parallel rating modules based on six elements: A, B, C, D, E, and F. Each rating module has four rating indicators: a, b, c, and d. These four rating indicators are represented by two binary numbers A1A0, where a=10, b=01, c=11, and d=00. The rating level of each indicator is input through the binary code A1A0, and after passing through a decoder, a full adder, a carry-lookahead adder, a numerical comparator, and a logic circuit consisting of multiple logic gates connected in series, the system outputs a comprehensive evaluation level of the granite pegmatite raw material: Level1, Level2, Level3, and Level4.
[0025] Among them, Level 1 granite pegmatite raw materials can be used to prepare high-purity quartz of grade 4N5 or higher, Level 2 granite pegmatite raw materials can be used to prepare high-purity quartz of grade 4N or higher, Level 3 granite pegmatite raw materials can be used to prepare high-purity quartz of grade 3N or higher, and Level 4 granite pegmatite raw materials are not recommended for development and utilization as high-purity quartz raw materials.
[0026] Alternatively, the decoder is a 74LS139 or 74HC139, capable of converting two binary A1A0 bits into a single binary digit.
[0027] Alternatively, the full adder adds the binary numbers output by the decoders of the six parallel rating modules, where S is the sum of the bits and C is the carry-in to the higher bits.
[0028] Alternatively, the carry-lookahead adder is a 74LS283 or a 74HC283, capable of adding the sum and carry of two full adders to calculate the number Na of rating a or the number Na+b of rating a+b among the six elements.
[0029] Alternatively, the numerical comparator is a 74LS85 or a 74HC85, capable of comparing the three-bit sum S2S1S0 output by the adder with (011). BOr (010) B By comparing, we can determine whether Na is not less than 3, whether Nb is not less than 3, and whether Nb is not less than 2.
[0030] Optionally, slice 1, slice 2, and slice 3 are all modules composed of the carry-lookahead adder and the numerical comparator, which can perform graded counting of the rating indicators of the six elements and compare the corresponding grade numbers.
[0031] Alternatively, slice 1 is used to calculate the number Na of a and to compare Na with (011). B =(3) D For comparison, when Na≥3, the overall grade of the sample is output as Level1; the slice 2 includes calculating the number of a+b (a or b) Na+b and comparing Na+b with (011). B =(3) D For comparison, when Na+b≥3, the overall grade of the sample is output as Level2; the number of a+b (a or b) Na+b in the slice 3 is calculated and Na+b is compared with (010). B =(2) D For comparison, if Na+b≥2, the overall level of the sample is output as Level3; otherwise, the overall level of the sample is output as Level4.
[0032] Compared with the prior art, the beneficial effects of the present invention include at least one of the following: (1) The quality evaluation method of granite pegmatite-type high-purity quartz provided by the present invention evaluates and screens granite pegmatite-type high-purity quartz raw materials through a comprehensive evaluation system and rating indicators. The method comprehensively considers key factors such as mineral composition, weathering degree, rock and mineral identification characteristics (embedding characteristics), physical beneficiation concentrate characteristics, physical beneficiation concentrate purity, and chemical beneficiation concentrate purity. It can effectively solve the problems of inconsistent evaluation standards for high-purity quartz sand and excessive reliance on single tests to verify the purification potential of raw materials. At the same time, it can also significantly reduce unnecessary waste in manpower, material resources, and financial resources.
[0033] (2) The present invention can quickly screen out raw materials with high-purity quartz purification potential during the production process, and classify and utilize raw materials of different grades of quartz, thus avoiding the cost waste of high-value utilization of low-grade quartz and the waste of raw materials of low-value utilization of high-grade quartz.
[0034] (3) This invention provides a quality rating system for high-purity quartz raw materials. The method is programmed by digital signal logic circuits to construct a mineralogical evaluation system for the purification potential of high-purity quartz. It covers the process end, detection end and rating end. It is a comprehensive evaluation system that integrates mineral genesis, impurity controllability and structural defects. The reliability of the evaluation system is confirmed by systematic testing of various quartz mineral samples from various regions in China. It provides an important reference for geological exploration and prospecting in China. In the future, it is expected to further propose an AI database model for the identification of high-purity quartz raw ore. Attached Figure Description
[0035] The above and other objects and / or features of the present invention will become clearer from the following description taken in conjunction with the accompanying drawings, in which: Figure 1 A flowchart of the method for evaluating the quality of high-purity granite pegmatite raw materials according to the present invention is shown.
[0036] Figure 2 A radar chart for evaluating the granite pegmatitic high-purity quartz raw material described in this invention is shown.
[0037] Figure 3 The diagram shows the logic design of the granite pegmatite high-purity quartz raw material quality rating system of the present invention.
[0038] Figure 4-1 A photograph showing the appearance and morphology of sample Q-1 raw ore is shown.
[0039] Figure 4-2 The XRD pattern of sample Q-1 raw ore is shown.
[0040] Figure 4-3 The rock and mineral identification diagram of sample Q-1 is shown.
[0041] Figure 4-4 The microstructure of the physically separated concentrate of sample Q-1 is shown.
[0042] Figure 5-1 A photograph of the appearance of sample Q-2 raw ore is shown.
[0043] Figure 5-2 The XRD pattern of sample Q-2 raw ore is shown.
[0044] Figure 5-3 The rock and mineral identification diagram of sample Q-2 is shown.
[0045] Figure 5-4 The microstructure of the physically separated concentrate of sample Q-2 is shown.
[0046] Figure 6-1 A photograph showing the appearance and morphology of sample Q-3 ore is shown.
[0047] Figure 6-2 The XRD pattern of sample Q-3 ore is shown.
[0048] Figure 6-3 The rock and mineral identification diagram of sample Q-3 is shown.
[0049] Figure 6-4 The microstructure of the physically separated concentrate of sample Q-3 is shown.
[0050] Figure 7-1 A photograph showing the appearance of sample Q-4 ore is shown.
[0051] Figure 7-2 The XRD pattern of sample Q-4 ore is shown.
[0052] Figure 7-3 The rock and mineral identification diagram of sample Q-4 is shown.
[0053] Figure 7-4 The microstructure of the physically separated concentrate of sample Q-4 is shown. Detailed Implementation
[0054] In the following text, a method, rating index and system for evaluating the quality of high-purity quartz raw materials of granite pegmatite type according to the present invention will be described in detail with reference to exemplary embodiments.
[0055] Exemplary Example 1 This exemplary embodiment provides a method for evaluating the quality of high-purity quartz raw materials from granite pegmatite, the evaluation process being as follows: Figure 1 As shown, the evaluation methods include receiving samples, sample preparation, observation of hand specimens, raw ore analysis, mineral processing tests, pure mineral analysis, high-purity tests, and high-purity product analysis. Specifically, the evaluation methods may include: S1. Analyze the mineral composition of the raw ore to obtain a mineral composition rating.
[0056] In this embodiment, the mineral composition rating of the raw ore includes four levels: a, b, c, and d. The main gangue mineral in the grade a raw ore is muscovite, with a small amount of feldspar. The main gangue mineral in the grade b raw ore is feldspar, with a small amount of muscovite or biotite. The grade c raw ore contains more than 5% of three or more gangue minerals, including feldspar, muscovite, biotite, tourmaline, and rutile. The grade d raw ore contains more than 5% of four or more gangue minerals, including feldspar, muscovite, biotite, tourmaline, rutile, anatase, and clay minerals. The feldspars include potassium feldspar, sodium feldspar, and calcium feldspar, as well as their isomorphous series products.
[0057] In this embodiment, the method for analyzing the mineral composition of the raw ore includes determining the mineral composition and chemical composition of the granite pegmatite raw ore by X-ray diffraction combined with X-ray fluorescence spectroscopy.
[0058] S2. Analyze the weathering degree of the raw ore to obtain a weathering degree rating.
[0059] In this embodiment, the weathering degree rating of the raw ore includes four levels: a, b, c, and d. The grade a raw ore has stable mineral crystallinity and no weathering traces. The grade b raw ore shows weathering on the surface and occasionally exhibits feldspar kaolinization characteristics. The grade c raw ore has a high degree of weathering, with clay minerals appearing in the crystal phase and the clay phase content exceeding 3%. The grade d raw ore is severely weathered and cannot maintain a blocky morphology, appearing as sandy or sandy ore particles.
[0060] In this embodiment, the analysis of the weathering degree of the raw ore is determined by sampling the appearance and morphological characteristics of the raw ore hand specimen.
[0061] S3. Analyze the mineral distribution state of the raw ore to obtain a mineral distribution state rating.
[0062] In this embodiment, the mineral embedding status rating of the raw ore is based on the embedding characteristics between quartz and gangue minerals in granite pegmatite, including four levels: a, b, c, and d. In the a-level raw ore, the quartz exhibits wavy extinction, and the mineral embedding is mainly composed of independent associated minerals. In the b-level raw ore, the quartz grains are intact, and the embedded minerals are mainly muscovite and feldspar filling the intercrystalline fissures of quartz. In the c-level raw ore, there are many embedded minerals (such as muscovite, feldspar, garnet, and tourmaline) inside the quartz grains, and the embedding size is above the micrometer level. In the d-level raw ore, there are many columnar embedded minerals (such as muscovite, feldspar, garnet, and tourmaline) inside the quartz grains, as well as needle-like micrometer / submicrometer-sized solid inclusions.
[0063] In this embodiment, the analysis of the mineral embedding state of the raw ore includes observing granite pegmatite ore slices using a transmitted, reflected, and polarized light microscope to identify the embedding state between gangue minerals and quartz, as well as the inclusion of impurities inside the quartz.
[0064] S4. Perform physical separation on the raw ore and analyze the morphological characteristics of the physical separation concentrate to obtain a morphological characteristic rating of the physical separation concentrate.
[0065] In this embodiment, the morphological characteristics rating of the physical beneficiation concentrate is based on the microscopic morphology of the concentrate obtained from the physical beneficiation of granite pegmatite, including four levels: a, b, c, and d. In level a physical beneficiation concentrate, the quartz grains are transparent and free of staining, with few solid inclusions inside the grains, and a small number of gas-liquid inclusions, mainly secondary / pseudo-secondary. In level b physical beneficiation concentrate, the quartz grains are transparent and have little surface staining, with few solid inclusions inside the grains, and a small number of gas-liquid inclusions. In level c physical beneficiation concentrate, the quartz grains show visible staining, with occasional dark particles mixed in, and a large number of solid or gas-liquid inclusions inside the grains. In level d physical beneficiation concentrate, the quartz grains show visible staining, with dark particles mixed in, and a large number of complex types of gas-liquid inclusions inside the grains, showing characteristics of original gas-liquid inclusions.
[0066] In this embodiment, the analysis of the morphological characteristics of the physical separation concentrate includes observing the quartz concentrate particles through a transmitted, reflected and polarized light microscope to identify the proportion of gangue minerals in the concentrate, the embedding characteristics of quartz inclusions, and the morphology and particle size of quartz particles.
[0067] In this embodiment, the physical separation concentrate is prepared from granite pegmatite ore through one or more non-chemical methods such as sand making, gravity separation, magnetic separation, flotation, color separation, and electrostatic separation.
[0068] S5. Analyze the SiO2 content of the physical beneficiation concentrate and obtain the SiO2 content rating of the physical beneficiation concentrate.
[0069] In this embodiment, the SiO2 content rating of the physical beneficiation concentrate is based on the impurity content of the concentrate obtained from the physical beneficiation of granite pegmatite, including four levels: a, b, c, and d. The SiO2 chemical purity of the grade a physical beneficiation concentrate is greater than 99.95%; the purity of the grade b physical beneficiation concentrate is greater than 99.9%; the purity of the grade c physical beneficiation concentrate is greater than 98%; and the purity of the grade d physical beneficiation concentrate is less than 98%.
[0070] S6. Perform chemical separation on the physically separated concentrate, and analyze the SiO2 content of the chemically separated concentrate to obtain the SiO2 content rating of the chemically separated concentrate.
[0071] In this embodiment, the SiO2 content rating of the chemically beneficiated concentrate is based on the impurity content of the concentrate obtained from the chemical beneficiation of granite pegmatite, including four levels: a, b, c, and d. Level a chemically beneficiated concentrate has a purity greater than 4N5 and its impurity chemical components are mainly K and Na. Level b chemically beneficiated concentrate has a purity greater than 4N and its impurity chemical components are mainly Al, K, Na, Fe, and Mg. Level c chemically beneficiated concentrate has a purity greater than 3N and its impurity chemical components are mainly Al, K, Na, Fe, Mg, Ca, and Ti. Level d chemically beneficiated concentrate has a purity lower than 3N and its impurity chemical components are complex; therefore, it is rated as level d.
[0072] In this embodiment, the chemically separated concentrate is a highly purified quartz sand obtained by purifying the physically separated concentrate through high-temperature acid leaching, chlorination roasting, and hot-press acid leaching.
[0073] In this embodiment, the analytical method for SiO2 content includes detecting the trace element chemical composition in high-purity quartz using ICP-OES (inductively coupled plasma optical emission spectrometry) or ICP-MS (inductively coupled plasma mass spectrometry). The SiO2 content is obtained by the difference method, i.e., w(SiO2) = (1 – w (杂质元素总量) ) × 100%.
[0074] S7. Summarize the rating results from steps S1-S6 to complete the quality evaluation of the granite pegmatite-type high-purity quartz raw material.
[0075] Exemplary Example 2 This exemplary embodiment provides a method for evaluating the quality of high-purity quartz raw materials of granite pegmatite type, the evaluation method may include the following steps: S1. Rating six indicators of granite pegmatite-type quartz raw materials.
[0076] In this embodiment, six groups of indicators—mineral composition, weathering degree, rock and mineral identification characteristics (intercalation characteristics), physical beneficiation concentrate characteristics, physical beneficiation concentrate purity, and chemical beneficiation concentrate purity—are graded. Each group of indicators is divided into four levels: a, b, c, and d, as shown in Table 1. Specifically: S11. Mineral composition analysis, evaluation, and grading of granite pegmatite ore: Representative granite pegmatite samples were selected and ground to below 200 mesh using an agate mortar. The mineral composition and chemical composition of the granite pegmatite ore were determined by X-ray diffraction combined with X-ray fluorescence spectroscopy. When the main gangue minerals in the analyzed mineral composition are muscovite and a small amount of feldspar, the grade is A; when the main gangue minerals are feldspar and a small amount of muscovite or biotite, the grade is B; when the content of gangue minerals in the ore is greater than 5% and there are 3 or more types of gangue minerals, including feldspar, muscovite, biotite, tourmaline, and rutile, the grade is C; when the content of gangue minerals in the ore is greater than 5% and there are 4 or more types of gangue minerals, including feldspar, muscovite, biotite, tourmaline, rutile, anatase, and clay minerals, the grade is D.
[0077] S12. Analyze, evaluate, and classify the weathering degree of granite pegmatite ore: Select representative granite pegmatite ore samples and determine the weathering degree of the ore by analyzing the appearance and morphological characteristics of the sampled raw ore specimens; when the mineral crystallinity is stable and there are no weathering traces in the analysis of the ore's weathering degree, its rating is Class A; when weathering occurs on the surface of the ore and feldspar and kaolinization characteristics are occasionally observed, its rating is Class B; when the ore has a high degree of weathering, clay minerals appear in the crystal phase, and the clay phase content exceeds 3%, its rating is Class C; when the weathering degree is severe and cannot maintain a massive morphology, appearing as sandy or dusty ore particles, its rating is Class D.
[0078] S13. Analyze, evaluate, and classify the mineral embedding state of granite pegmatite ore: Select representative granite pegmatite ore samples, prepare thin sections (slices), and observe and analyze each area of the slices using a transmitted, reflected, and polarized light microscope to identify the embedding state between gangue minerals and quartz, as well as the inclusion of impurities within the quartz. When the quartz exhibits wavy extinction and the mineral embedding state is dominated by independent associated minerals, its rating is A. If the quartz grains are intact and the embedded minerals are mainly muscovite and feldspar filling the intercrystalline fissures of quartz, its rating is B. If there are many embedded minerals (muscovite, feldspar, garnet, tourmaline) within the quartz grains, and the embedding size is above the micrometer level, its rating is C. If there are many columnar embedded minerals (muscovite, feldspar, garnet, tourmaline) and needle-like micrometer / submicrometer-sized solid inclusions within the quartz grains, its rating is D.
[0079] S14. Analyze, evaluate, and classify the morphological characteristics of the physical beneficiation concentrate of granite pegmatite: Select representative granite pegmatite samples and subject them to physical beneficiation processes such as crushing, grinding-screening, magnetic separation, and flotation to obtain the physical beneficiation concentrate of granite pegmatite. Observe the microscopic morphology of the concentrate to identify the proportion of gangue minerals, the embedding characteristics of quartz inclusions, and the morphology and size of quartz particles. When the microscopic morphology analysis shows that the quartz grains are transparent and free of discoloration, with few solid inclusions inside the grains, and a small number of gas-liquid inclusions, and are of secondary importance... If the quartz grains are predominantly composed of Neogene / pseudo-Secondary-Generation inclusions, they are rated as Class A; if the quartz grains are clear with little surface staining, few solid inclusions inside the grains, and a small number of gas-liquid inclusions, they are rated as Class B; if the quartz grains show staining, with occasional dark particles mixed in, and a large number of solid or gas-liquid inclusions inside the grains, they are rated as Class C; if the quartz grains show staining, with dark particles mixed in, and a large number of complex types of gas-liquid inclusions inside the grains, exhibiting characteristics of original gas-liquid inclusions, they are rated as Class D.
[0080] S15. Analyze, evaluate, and classify the SiO2 content of the physical beneficiation concentrate of granite pegmatite: Analyze the SiO2 content of the obtained physical beneficiation concentrate to identify the degree of liberation and removal of gangue minerals by the previous physical beneficiation and the impurity content of the physical beneficiation concentrate; when the SiO2 content of the flotation concentrate is greater than 99.95%, it is rated as Class A; when the purity is greater than 99.9%, it is rated as Class B; when the purity is greater than 98%, it is rated as Class C; when the purity is less than 98%, it is rated as Class D.
[0081] S16. Analyze, evaluate, and classify the SiO2 content of the chemically beneficiated concentrate from granite pegmatite: The obtained physical beneficiation concentrate is further purified by high-temperature acid leaching, chlorination roasting, and hot-pressing acid leaching to obtain the chemically beneficiated concentrate, i.e., high-purity quartz sand. The chemical composition of this concentrate is analyzed: When the purity of the high-purity quartz sand is greater than 4N5 and the main chemical components of impurities are K and Na, its rating is Class A; when the purity of the high-purity quartz sand is greater than 4N and the main chemical components of impurities are Al, K, Na, Fe, and Mg, its rating is Class B; when the purity of the high-purity quartz sand is greater than 3N and the main chemical components of impurities are Al, K, Na, Fe, Mg, Ca, and Ti, its rating is Class C; when the purity of the high-purity quartz sand is less than 3N and the chemical composition of impurities is complex, its rating is Class D. S2. A comprehensive evaluation is derived based on the rating of various indicators of high-purity quartz raw materials.
[0082] Of the six rating indicators above, at least three categories with a rating of A or above can be considered as first-grade high-purity quartz raw materials. After optimizing the purification process, high-purity quartz of grade 4N5 or above can be prepared. Of the six rating indicators above, at least three categories of materials with a rating of B or above can be considered as secondary high-purity quartz raw materials. After optimizing the purification process, high-purity quartz of grade 4N or above can be prepared. Of the six rating indicators above, at least two of them are classified as Class B or above and can be considered as Grade III high-purity quartz raw materials. After optimizing the purification process, high-purity quartz of Grade 3N or above can be prepared. Of the six rating categories above, those with fewer than two categories of rating B or above are not recommended for development as high-purity quartz raw materials.
[0083] Table 1 Evaluation Indicators for Quartz Raw Materials from Granite Pegmatite
[0084]
[0085] Exemplary Example 3 This exemplary embodiment provides a quality rating index for high-purity quartz raw materials of granite pegmatite type, which is applicable to the quality evaluation method of high-purity quartz raw materials of granite pegmatite type described in Exemplary Embodiment 1 or Exemplary Embodiment 2.
[0086] In this embodiment, the rating index includes six elements: A - mineral composition of the raw ore, B - weathering degree of the raw ore, C - mineral dissemination state of the raw ore, D - morphological characteristics of the physically separated concentrate, E - SiO2 content of the physically separated concentrate, and F - SiO2 content of the chemically separated concentrate. The rating of each of the six elements includes four levels: a, b, c, and d. The comprehensive rating result yields a quality evaluation of the granite pegmatite-type high-purity quartz raw material. Materials with at least three grades of A are classified as Grade 1 high-purity quartz raw materials; Materials with at least three grades of B or higher are classified as secondary high-purity quartz raw materials; Materials with at least two grades of B or higher are classified as Grade III high-purity quartz raw materials; It is recommended that fewer than two of grade B or higher be developed and utilized as non-high-purity quartz raw materials.
[0087] In this embodiment, the primary high-purity quartz raw material can be used to prepare high-purity quartz of grade 4N5 or higher after the purification process is optimized. The secondary high-purity quartz raw material can be used to prepare high-purity quartz of grade 4N or higher after the purification process is optimized. The three-level high-purity quartz raw materials can be used to prepare high-purity quartz of grade 3N or higher after the purification process is optimized.
[0088] Exemplary Example 4 This exemplary embodiment provides a quality rating system for high-purity granite pegmatite-type quartz raw materials. The evaluation system can implement the quality evaluation method for granite pegmatite-type quartz raw materials described in Exemplary Embodiment 1 or Exemplary Embodiment 2, and is based on the quality rating indicators for high-purity granite pegmatite-type quartz raw materials described in Exemplary Embodiment 3. The logical design of the quality rating system is as follows: Figure 3 As shown.
[0089] In this embodiment, the rating system adopts a semi-quantitative threshold grading evaluation method. The indicators for evaluating and grading six elements of granite pegmatite ore and its physical and chemical beneficiation concentrate are programmable through digital signal logic circuits. The rating system is a multi-index rating system composed of a decoder, a full adder, a carry-lookahead adder, a numerical comparator, and a counter.
[0090] In this embodiment, the rating system is set as six parallel rating modules based on six elements: A, B, C, D, E, and F. Each rating module has four rating indicators: a, b, c, and d. The four rating indicators are represented by two binary numbers A1A0, where a=10, b=01, c=11, and d=00. The rating level of each indicator is input through the binary code A1A0, and after passing through a decoder, a full adder, a carry-lookahead adder, a numerical comparator, and a logic circuit with multiple logic gates connected in series, the system outputs a comprehensive evaluation level of the granite pegmatite raw material: Level1, Level2, Level3, and Level4.
[0091] Among them, Level 1 granite pegmatite raw materials can be used to prepare high-purity quartz of grade 4N5 or higher, Level 2 granite pegmatite raw materials can be used to prepare high-purity quartz of grade 4N or higher, Level 3 granite pegmatite raw materials can be used to prepare high-purity quartz of grade 3N or higher, and Level 4 granite pegmatite raw materials are not recommended for development and utilization as high-purity quartz raw materials.
[0092] In this embodiment, the decoder is a 74LS139 or a 74HC139, which can convert two binary A1A0 into one binary number (Ga, Gb...).
[0093] In this embodiment, the full adder adds the binary numbers (Ga / Gb) output by the decoders of the six parallel rating modules, where S is the sum of the bits and C is the carry-in to the higher bits.
[0094] In this embodiment, the carry-lookahead adder is a 74LS283 or a 74HC283, which can add the sum of the two full adders and the carry-in number to calculate the number of ratings a or the number of ratings a+b Na+b among the six elements.
[0095] In this embodiment, the numerical comparator is a 74LS85 or a 74HC85, which can compare the three-bit sum S2S1S0 output by the adder with (011). B Or (010) B By comparing, we can determine whether Na is not less than 3, whether Nb is not less than 3, and whether Nb is not less than 2.
[0096] In this embodiment, chip 1, chip 2, and chip 3 are all modules composed of the carry-lookahead adder and the numerical comparator, which can perform graded counting of the rating indicators of the six elements and compare the corresponding grade numbers.
[0097] In this embodiment, slice 1 is used to calculate the number Na of a and to compare Na with (011). B =(3) D For comparison, when Na≥3, the overall grade of the sample is output as L1 (Level 1); the slice 2 includes calculating the number of a+b (a or b) Na+b and comparing Na+b with (011). B =(3) D For comparison, when Na+b≥3, the overall grade of the sample is output as L2 (Level 2); the slice 3 calculates the number of a+b (a or b) Na+b and compares Na+b with (010). B =(2) D For comparison, if Na+b≥2, the overall level of the sample is output as L3 (Level 3); otherwise, the overall level of the sample is output as L4 (Level 4).
[0098] To better understand the exemplary embodiments of the present invention described above, further explanation is provided below with reference to specific examples.
[0099] Example 1 This example applies the quality evaluation method, rating index, and system for high-purity granite pegmatite raw materials described in this invention to evaluate the impurity content of a certain high-purity granite pegmatite raw material, thereby determining its raw material quality. The process includes the following steps: 1) Representative granite pegmatite ore sample Q-1 was selected and ground to below 200 mesh using an agate mortar. The mineral composition and chemical composition of the raw granite pegmatite ore were determined by X-ray diffraction combined with X-ray fluorescence spectroscopy analysis. Figure 4-2 As shown in Table 2-1, the mineral composition of this sample is complex. It is a typical granite pegmatite-type quartz ore containing tourmaline. The main gangue minerals are silicate minerals, including microcline, albite, muscovite, tourmaline, etc.
[0100] Table 2-1 Summary of the results of the major chemical composition analysis of sample Q-1 (%)
[0101] 2) Select representative granite pegmatite ore sample Q-1, and determine the degree of weathering of the ore by analyzing the appearance and morphological characteristics of the sampled raw ore specimens, such as... Figure 4-1 As shown, the sample exhibits an irregular fragment shape. The irregular shape at the cross-section reveals the rock formation process and its weathering and erosion history in the natural environment, showing a tendency towards pulverization and clayification.
[0102] 3) Select representative granite pegmatite samples Q-1, prepare thin sections (slices), and observe and analyze each area of the slices using a transmitted, reflected, and polarized light microscope to identify the intergrowth of gangue minerals and quartz, as well as the inclusion of impurities within the quartz. Figure 4-3 As shown, the quartz crystals are intact and closely embedded with other gangue minerals (feldspar, mica, tourmaline). The quartz contains acicular transparent minerals and has a high content of fluid inclusions, which are mostly distributed in planar and linear forms.
[0103] 4) Select representative granite pegmatite ore sample Q-1 and process it through crushing, grinding-screening, magnetic separation, and flotation to obtain a physical separation concentrate of granite pegmatite. Observe the microstructure of this concentrate to identify the proportion of gangue minerals, the embedding characteristics of quartz inclusions, and the morphology and size of quartz particles. Figure 4-4 As shown, no associated minerals were found under high magnification, but there were many inclusions in the quartz grains. The inclusions were mostly linear and star-shaped distributed inside the quartz. Under high magnification, the inclusions were mainly gas-liquid inclusions, but there were also solid inclusions with a size of about 10µm.
[0104] 5) The SiO2 content of the physical beneficiation concentrate obtained in step (4) is analyzed to identify the degree of dissociation and removal of gangue minerals by the previous physical beneficiation and the impurity content of the physical beneficiation concentrate. As shown in Table 2-2, the SiO2 content is 99.9%.
[0105] Table 2-2 Summary of Impurity Element Content and SiO2 Content in Physically Separated Concentrate of Sample Q-1 (ppm)
[0106] 6) The physical beneficiation concentrate obtained in step (4) is further purified by high-temperature acid leaching, chlorination roasting, and hot-press acid leaching to obtain chemical beneficiation concentrate. The chemical composition of the chemical beneficiation concentrate is analyzed. The chemical composition test data are shown in Table 2-3. After acid leaching, the SiO2 content of the quartz sand is 99.98%, and its impurity chemical composition is mainly Al, K and Ti.
[0107] Table 2-3 Chemical composition (ppm) of concentrate from sample Q-1 chemical separation
[0108] 7) The rating results for mineral composition, weathering degree, mineral dissemination state, morphological characteristics of physically beneficiated concentrate, purity of physically beneficiated concentrate, and purity of chemically beneficiated concentrate are shown in Table 2-4. The corresponding radar charts for refining potential evaluation are shown below. Figure 2 As shown.
[0109] Table 2-4 Rating Results of Each Indicator
[0110] Sample Q-1 contains more than three main gangue minerals, including biotite and tourmaline. The quartz grains contain a large number of embedded minerals (mica, feldspar, garnet, and tourmaline) with sizes larger than micrometers. The quartz grains show visible color infiltration, with occasional dark particles mixed in. There are a large number of solid or gas-liquid inclusions inside the grains. The flotation concentrate purity is about 98%, while the chemically separated concentrate purity does not reach 3N. The chemical composition of the impurities is mainly Al, K, Na, Fe, Mg, Ca, and Ti.
[0111] 8) Based on the rating results table above, input the results into the evaluation system in binary code. Input the binary codes 11, 01, 11, 11, 01, and 11 respectively into the evaluation system for ABCDEF. The system will then obtain a comprehensive rating of L3. If the sample has at least two ratings above class b, it can be considered a grade 3 high-purity quartz raw material. After optimizing the purification process, high-purity quartz of grade 3N or higher can be prepared.
[0112] Subsequent research on the purification process optimization revealed that 3N8 grade high-purity quartz could be prepared by crushing, selective grinding, scrubbing, desliming, flotation, microwave, acid leaching, secondary flotation, calcination, and hot-pressing acid leaching. However, the process cost was too high and the yield was low, which is consistent with the results obtained from the evaluation and screening in this example.
[0113] Example 2 This example applies the quality evaluation method, rating index, and system for high-purity granite pegmatite raw materials described in this invention to evaluate a certain type of high-purity granite pegmatite, thereby determining its raw material quality. The process includes the following steps: 1) Representative granite pegmatite ore sample Q-2 was selected and ground to below 200 mesh using an agate mortar. The mineral composition and chemical composition of the raw granite pegmatite ore were determined by X-ray diffraction combined with X-ray fluorescence spectroscopy analysis. Figure 5-2 As shown in Table 3-1, the mineral composition of this sample is simple, and it is a typical white granite quartz ore. The main gangue minerals are silicate minerals, including albite and muscovite.
[0114] Table 3-1 Summary of the results of the major chemical composition analysis of sample Q-2 (%)
[0115] 2) Select representative granite pegmatite ore sample Q-2, and determine the degree of weathering of the ore by analyzing the appearance and morphological characteristics of the sampled raw ore specimens, such as... Figure 5-1 As shown, the sample is hard overall, with feldspar and quartz interwoven in the inner layer, and weathered powder mica residue visible on the outer layer, along with some clay-like minerals and moss-like vegetation.
[0116] 3) Select representative granite pegmatite samples Q-2, prepare thin sections (slices), and observe and analyze each area of the slices using a transmitted, reflected, and polarized light microscope to identify the intergrowth of gangue minerals and quartz, as well as the inclusion of impurities within the quartz. Figure 5-3 As shown, the quartz grains are intact, and the edges of the inlays with other gangue minerals (feldspar, mica) are relatively smooth. The fluid inclusions inside the quartz are mostly distributed in a linear pattern and are relatively small in size.
[0117] 4) Select representative granite pegmatite ore sample Q-2 and process it through crushing, grinding-screening, magnetic separation, and flotation to obtain a physical separation concentrate of granite pegmatite. Observe the microstructure of this concentrate to identify the proportion of gangue minerals, the embedding characteristics of quartz inclusions, and the morphology and size of quartz particles. Figure 5-4 As shown, no associated minerals were found under high magnification, but there were many inclusions in the quartz grains. The inclusions were mostly linear and star-shaped distributed inside the quartz. Under high magnification, the inclusions were mainly gas-liquid inclusions, but there were also solid inclusions with a size of about 20µm.
[0118] 5) The SiO2 content of the physical beneficiation concentrate obtained in step (4) is analyzed to identify the degree of dissociation and removal of gangue minerals by the previous physical beneficiation and the impurity content of the physical beneficiation concentrate. As shown in Table 3-2, the SiO2 content is 99.97%.
[0119] Table 3-2 Summary of Impurity Element Content and SiO2 Content in Physically Beneficiated Concentrate of Sample Q-2 (ppm)
[0120] 6) The physical beneficiation concentrate obtained in step (4) is further purified by high-temperature acid leaching, chlorination roasting, and hot-press acid leaching to obtain chemical beneficiation concentrate. The chemical composition of the chemical beneficiation concentrate is analyzed. The chemical composition test data are shown in Table 3-3. After acid leaching, the SiO2 content of the quartz sand is 99.994%, and its impurity chemical composition is mainly Al and Ti.
[0121] Table 3-3 Chemical composition (ppm) of concentrate from sample Q-2 chemical separation
[0122] 7) The rating results for mineral composition, weathering degree, mineral dissemination state, morphological characteristics of physically beneficiated concentrate, purity of physically beneficiated concentrate, and purity of chemically beneficiated concentrate are shown in Table 3-4. The corresponding radar charts for refining potential evaluation are shown below. Figure 2 As shown.
[0123] Table 3-4 Rating Results of Each Indicator
[0124] Sample Q-2 mainly consists of feldspar and a small amount of mica. The minerals are crystallized and stable, with no signs of weathering. The quartz grains are intact, and the embedded minerals are mainly muscovite and feldspar filling the intercrystalline fissures of the quartz. The quartz grains and gangue minerals are regularly and evenly interspersed. The quartz grains are transparent and free of staining. A small number of solid inclusions and a large number of gas-liquid inclusions are visible inside. The number of gas-liquid inclusions is small and they are mainly secondary / pseudo-secondary inclusions. The purity of the flotation concentrate is greater than 99.95%, and the purity of the chemically separated concentrate is greater than 4N. The chemical composition of the impurities is mainly Al and Ti.
[0125] 8) Based on the rating results table above, input the results into the evaluation system in binary code. Input the binary codes 01, 01, 01, 01, 11, and 01 respectively into the evaluation system for ABCDEF. The system will then obtain a comprehensive evaluation L2. If the sample has at least 3 ratings above class b, it can be considered a secondary high-purity quartz raw material. After optimizing the purification process, high-purity quartz of grade 4N or higher can be prepared.
[0126] Subsequent research on the purification process optimization revealed that after crushing and grinding, scrubbing and desliming, flotation, acid leaching, chlorination roasting, and hot pressing acid leaching, high-purity quartz of grade 4N5 can be prepared, which is consistent with the results obtained from the evaluation and screening in this embodiment.
[0127] Example 3 This example applies the quality evaluation method, rating index, and system for high-purity granite pegmatite raw materials described in this invention to evaluate a certain type of high-purity granite pegmatite, thereby determining its raw material quality. The process includes the following steps: 1) Representative granite pegmatite ore sample Q-3 was selected and ground to below 200 mesh using an agate mortar. The mineral composition and chemical composition of the raw granite pegmatite ore were determined by X-ray diffraction combined with X-ray fluorescence spectroscopy analysis. Figure 6-2 As shown in Table 4-1, the mineral composition of this sample is simple, and it is a typical granite quartz ore. The main gangue minerals are silicate minerals, including microcline, albite, and muscovite.
[0128] Table 4-1 Summary of the results of the major chemical composition analysis of sample Q-3 (%)
[0129] 2) Select representative granite pegmatite ore sample Q-3, and determine the degree of weathering of the ore by analyzing the appearance and morphological characteristics of the sampled raw ore specimens, such as... Figure 6-1 As shown, the sample is hard overall, with quartz crystal clusters exposed on the outer surface, indicating good crystallinity. The surface of the raw ore has feldspar dissociation surfaces and flaky mica layers.
[0130] 3) Select representative granite pegmatite samples Q-3, prepare thin sections (slices), and observe and analyze each area of the slices using a transmitted light, reflected light, and polarized light microscope to identify the intergrowth of gangue minerals and quartz, as well as the inclusion of impurities within the quartz. Figure 6-3 As shown, the quartz crystals are intact and relatively dispersed from other gangue minerals (feldspar, mica), but the edges of the inclusions are smooth. The fluid inclusions inside the quartz are mostly distributed in a linear pattern and are small in size, while solid inclusions are visible in some areas.
[0131] 4) Select representative granite pegmatite ore sample Q-3 and process it through crushing, grinding-screening, magnetic separation, and flotation to obtain a physical separation concentrate of granite pegmatite. Observe the microstructure of this concentrate to identify the proportion of gangue minerals, the embedding characteristics of quartz inclusions, and the morphology and size of quartz particles. Figure 6-4 As shown, no associated minerals were found under high magnification. The quartz grains were relatively pure, with inclusions in a small number of grains. The inclusions were mostly distributed in a star-like pattern inside the quartz. Under high magnification, the inclusions were mainly gas-liquid inclusions, and no obvious solid inclusions were observed.
[0132] 5) The SiO2 content of the physical beneficiation concentrate obtained in step (4) is analyzed to identify the degree of dissociation and removal of gangue minerals by the previous physical beneficiation and the impurity content of the physical beneficiation concentrate. As shown in Table 4-2, the SiO2 content is 99.95%.
[0133] Table 4-2 Summary of Impurity Element Content and SiO2 Content in Physically Beneficiated Concentrate of Sample Q-3 (ppm)
[0134] 6) The physical beneficiation concentrate obtained in step (4) is further purified by high-temperature acid leaching, chlorination roasting, and hot-press acid leaching to obtain chemical beneficiation concentrate. The chemical composition of the chemical beneficiation concentrate is analyzed. The chemical composition test data are shown in Table 4-3. After acid leaching, the SiO2 content of the quartz sand is 99.998%, and the chemical composition of its impurities is mainly Al.
[0135] Table 4-3 Chemical composition (ppm) of concentrate from sample Q-3 chemical separation
[0136] 7) The rating results for mineral composition, weathering degree, mineral dissemination state, morphological characteristics of physically beneficiated concentrate, purity of physically beneficiated concentrate, and purity of chemically beneficiated concentrate are shown in Table 4-4. The corresponding radar charts for refining potential evaluation are shown below. Figure 2 As shown.
[0137] Table 4-4 Rating Results of Each Indicator
[0138] The main gangue minerals in sample Q-3 are feldspar and a small amount of mica. No weathering was observed on the surface of the ore, with occasional kaolinization of feldspar. Quartz showed wavy extinction. The mineral distribution was mainly as independent associated minerals. The quartz grains were clear and unstained. Solid inclusions were rare inside the grains. Gas-liquid inclusions were few in number and mainly secondary / pseudo-secondary inclusions. The purity of the flotation concentrate was greater than 99.95%, and the purity of the chemically separated concentrate was greater than 4N8. The chemical composition of the impurities was mainly Al.
[0139] 8) Based on the rating results table above, input the results into the evaluation system in binary code. Input the binary codes 01, 01, 01, 11, 11, and 11 respectively into the evaluation system for ABCDEF. The system will then obtain a comprehensive rating of L1. If the sample has at least 3 ratings above class a, it can be considered a first-grade high-purity quartz raw material. After optimizing the purification process, high-purity quartz of grade 4N5 or higher can be prepared.
[0140] Subsequent research on the purification process optimization revealed that after crushing and grinding, scrubbing and desliming, flotation, calcination and water quenching, acid leaching, chlorination roasting, and hot pressing acid leaching, high-purity quartz of grade 4N8 can be prepared. This is consistent with the results obtained from the evaluation and screening in this embodiment, which shows that high-purity quartz of grade 4N5 and above can be prepared with high yield and investment payback period.
[0141] Example 4 This example applies the quality evaluation method, rating index, and system for high-purity granite pegmatite raw materials described in this invention to evaluate a certain type of high-purity granite pegmatite, thereby determining its raw material quality. The process includes the following steps: 1) Representative granite pegmatite ore sample Q-4 was selected and ground to below 200 mesh using an agate mortar. The mineral composition and chemical composition of the raw granite pegmatite ore were determined by X-ray diffraction combined with X-ray fluorescence spectroscopy analysis. Figure 7-2As shown in Table 5-1, the mineral composition of this sample is complex, with the main gangue minerals being plagioclase, muscovite, biotite, kaolinite, and tourmaline.
[0142] Table 5-1 Summary of the results of the major chemical composition analysis of sample Q-4 (%)
[0143] 2) Select representative granite pegmatite ore sample Q-4, and determine the degree of weathering of the ore by analyzing the appearance and morphological characteristics of the sampled raw ore specimens, such as... Figure 7-1 As shown, the sample exhibits an amorphous powdery appearance, with a loose surface texture on the quartz grains, revealing the rock's formation process and its weathering and erosion history in the natural environment, with obvious pulverization and clayification trends.
[0144] 3) Select representative granite pegmatite samples Q-4, prepare thin sections (slices), and observe and analyze each area of the slices using a transmitted, reflected, and polarized light microscope to identify the intergrowth of gangue minerals and quartz, as well as the inclusion of impurities within the quartz. Figure 7-3 As shown, the contact between quartz and gangue minerals is often irregular, intersecting or serrated, etc. Quartz contains many opaque fine-grained minerals, mostly distributed in a planar manner.
[0145] 4) Select representative granite pegmatite ore sample Q-4 and process it through crushing, grinding-screening, magnetic separation, and flotation to obtain a physical separation concentrate of granite pegmatite. Observe the microstructure of this concentrate to identify the proportion of gangue minerals, the embedding characteristics of quartz inclusions, and the morphology and size of quartz particles. Figure 7-4 As shown, other associated minerals can be seen under high magnification, and there are obvious and numerous inclusions in the quartz grains. The inclusions are mostly distributed in the interior of the quartz in a linear and star-like pattern. Under high magnification, the inclusions are mainly fine gas-liquid inclusions and large-diameter solid inclusions.
[0146] 5) The SiO2 content of the physical beneficiation concentrate obtained in step (4) is analyzed to identify the degree of dissociation and removal of gangue minerals by the previous physical beneficiation and the impurity content of the physical beneficiation concentrate. As shown in Table 5-2, the SiO2 content is 98%.
[0147] Table 5-2 Summary of Impurity Element Content and SiO2 Content in Physically Beneficiated Concentrate of Sample Q-4 (ppm)
[0148] 6) The physical beneficiation concentrate obtained in step (4) is further purified by high-temperature acid leaching, chlorination roasting, and hot-press acid leaching to obtain chemical beneficiation concentrate. The chemical composition of the chemical beneficiation concentrate is analyzed. The chemical composition test data are shown in Table 5-3. After acid leaching, the SiO2 content of the quartz sand is 99.96%, and its impurity chemical composition is mainly Al, K, Na, Fe, Mg, Ca and Ti.
[0149] Table 5-3 Chemical composition (ppm) of concentrate from sample Q-4 chemical separation
[0150] 7) The rating results for mineral composition, weathering degree, mineral dissemination state, morphological characteristics of physically beneficiated concentrate, purity of physically beneficiated concentrate, and purity of chemically beneficiated concentrate are shown in Table 5-4. The corresponding radar charts for refining potential evaluation are shown below. Figure 2 As shown.
[0151] Table 5-4 Rating Results of Each Indicator
[0152] Sample Q-4 contains more than three main gangue minerals, including biotite and tourmaline. The quartz grains contain a large number of embedded minerals (mica, feldspar, garnet, and tourmaline) with sizes larger than micrometers. The quartz grains show visible color infiltration, with occasional dark particles mixed in. There are a large number of solid or gas-liquid inclusions visible inside the grains. The flotation concentrate purity is about 98%, while the chemically separated concentrate purity does not reach 4N. The chemical composition of the impurities is mainly Al, K, Na, Fe, Mg, Ca, and Ti.
[0153] 8) Based on the rating results table above, input the results into the evaluation system in binary code. Input the binary codes 11, 00, 11, 00, 11, and 11 for ABCDEF in the evaluation system. The system will then generate a comprehensive rating of L4. If a candidate has fewer than two ratings above class b, it is not recommended for development as a high-purity quartz raw material.
[0154] Subsequent research on the purification process optimization revealed that after crushing, selective grinding, scrubbing, desliming, flotation, microwave, acid leaching, secondary flotation, calcination, and hot-pressing acid leaching, the highest purity quartz that could be obtained was 3N6 grade. However, the process cost was too high and the yield was low, which is consistent with the results obtained from the evaluation and screening in this embodiment.
[0155] Although the present invention has been described above in conjunction with exemplary embodiments and accompanying drawings, those skilled in the art should understand that various modifications can be made to the above embodiments without departing from the spirit and scope of the claims.
Claims
1. A method for evaluating the quality of high-purity quartz raw materials of granite pegmatite type, characterized in that, The evaluation methods include: 1) Analyze the mineral composition of the raw ore to obtain a mineral composition rating; 2) Analyze the weathering degree of the raw ore to obtain a weathering degree rating for the raw ore; 3) Analyze the mineral distribution pattern of the raw ore to obtain a mineral distribution pattern rating. 4) Perform physical separation on the raw ore and analyze the morphological characteristics of the physical separation concentrate to obtain a morphological characteristic rating of the physical separation concentrate; 5) Analyze the SiO2 content of the physical beneficiation concentrate to obtain the SiO2 content rating of the physical beneficiation concentrate; 6) Perform chemical separation on the physically separated concentrate, and analyze the SiO2 content of the chemically separated concentrate to obtain the SiO2 content rating of the chemically separated concentrate; 7) Summarize the rating results from steps 1)-6) to complete the quality evaluation of granite pegmatite-type high-purity quartz raw materials.
2. The method for evaluating the quality of high-purity quartz raw materials of granite pegmatite type according to claim 1, characterized in that, The mineral composition rating of the raw ore includes four levels: a, b, c, and d. Level a raw ore primarily contains muscovite as its gangue mineral, with a small amount of feldspar. Level b raw ore primarily contains feldspar as its gangue mineral, with a small amount of muscovite or biotite. Level c raw ore contains more than 5% of three or more gangue minerals, including feldspar, muscovite, biotite, tourmaline, and rutile. Level d raw ore contains more than 5% of four or more gangue minerals, including feldspar, muscovite, biotite, tourmaline, rutile, anatase, or clay minerals. The feldspars include potassium feldspar, sodium feldspar, and calcium feldspar and their isomorphic series products; The weathering degree rating of the raw ore includes four levels: a, b, c, and d. Level a raw ore has stable mineral crystallinity and no weathering traces. Level b raw ore shows weathering on the surface and occasionally feldspar and kaolinization characteristics. Level c raw ore has a high degree of weathering, with clay minerals appearing in the crystal phase and the clay phase content exceeding 3%. Level d raw ore is severely weathered and cannot maintain a blocky morphology, appearing as sandy or sandy ore particles.
3. The method for evaluating the quality of high-purity quartz raw materials of granite pegmatite type according to claim 1, characterized in that, The mineral embedding status rating of the raw ore is based on the embedding characteristics between quartz and gangue minerals in granite pegmatites, including four levels: a, b, c, and d. In level a raw ore, quartz exhibits wavy extinction, and the mineral embedding is mainly composed of independent associated minerals. In level b raw ore, quartz grains are intact, and the embedded minerals are mainly muscovite and feldspar filling the intercrystalline fissures of quartz. In level c raw ore, there are many embedded minerals inside the quartz grains, and the embedding size is above the micrometer level. In level d raw ore, there are many columnar embedded minerals inside the quartz grains, as well as needle-like micrometer / submicrometer-sized solid inclusions.
4. The method for evaluating the quality of high-purity quartz raw materials of granite pegmatite type according to claim 1, characterized in that, The morphological characteristics rating of the physical beneficiation concentrate is based on the microscopic morphology of the concentrate obtained from the physical beneficiation of granite pegmatite, including four levels: a, b, c, and d. Level a physical beneficiation concentrate has bright quartz grains without discoloration, few solid inclusions inside the grains, and a small number of gas-liquid inclusions, mainly secondary / pseudo-secondary. Level b physical beneficiation concentrate has bright quartz grains with little surface staining, few solid inclusions inside the grains, and a small number of gas-liquid inclusions. Level c physical beneficiation concentrate has quartz grains with visible discoloration, occasionally with dark particles mixed in, and a large number of solid or gas-liquid inclusions inside the grains. Level d physical beneficiation concentrate has quartz grains with visible discoloration, with dark particles mixed in, and a large number of complex types of gas-liquid inclusions inside the grains, showing characteristics of original gas-liquid inclusions.
5. The method for evaluating the quality of high-purity quartz raw materials of granite pegmatite type according to claim 1, characterized in that, The SiO2 content rating of the physical beneficiation concentrate is based on the impurity content of the concentrate obtained from the physical beneficiation of granite pegmatite, and includes four levels: a, b, c, and d. Level a physical beneficiation concentrate has a SiO2 chemical purity greater than 99.95%; level b physical beneficiation concentrate has a purity greater than 99.9%; level c physical beneficiation concentrate has a purity greater than 98%; and level d physical beneficiation concentrate has a purity less than 98%. The SiO2 content rating of the chemically beneficiated concentrate is based on the impurity content of the concentrate obtained from the chemical beneficiation of granite pegmatite, and includes four levels: a, b, c, and d. Level a chemically beneficiated concentrate has a purity greater than 4N5, and the main chemical components of the impurities are K and Na. Level b chemically beneficiated concentrate has a purity greater than 4N, and the main chemical components of the impurities are Al, K, Na, Fe, and Mg. Level c chemically beneficiated concentrate has a purity greater than 3N, and the main chemical components of the impurities are Al, K, Na, Fe, Mg, Ca, and Ti. Level d chemically beneficiated concentrate has a purity less than 3N and complex impurity chemical composition, and is therefore rated as level d.
6. The method for evaluating the quality of high-purity quartz raw materials of granite pegmatite type according to claim 1, characterized in that, Step 1) The method for analyzing the mineral composition of the raw ore includes determining the mineral composition and chemical composition of the granite pegmatite raw ore by X-ray diffraction combined with X-ray fluorescence spectroscopy. Step 2) The analysis of the weathering degree of the raw ore is determined by sampling the appearance and morphological characteristics of the raw ore hand specimens; Step 3) The analysis of the mineral distribution state of the raw ore includes observing granite pegmatite ore slices through a transmitted, reflected and polarized light microscope to identify the distribution of gangue minerals and quartz and the inclusion of impurities inside the quartz.
7. The method for evaluating the quality of high-purity quartz raw materials of granite pegmatite type according to claim 1, characterized in that, The analysis of the morphological characteristics of the physical separation concentrate includes observing quartz concentrate particles through transmitted, reflected and polarized light microscopes to identify the proportion of gangue minerals in the concentrate, the embedding characteristics of quartz inclusions, and the morphology and particle size of quartz particles. The physical separation concentrate is prepared from granite pegmatite ore through one or more non-chemical methods, such as sand making, gravity separation, magnetic separation, flotation, color separation, and electrostatic separation. The chemically separated concentrate is a highly purified quartz sand obtained by purifying the physically separated concentrate through high-temperature acid leaching, chlorination roasting, and hot-press acid leaching.
8. A quality rating index for high-purity quartz raw material of granite pegmatite type, characterized in that, The rating index is applicable to the quality evaluation method for granite pegmatite-type high-purity quartz raw materials as described in any one of claims 1-7. The rating index includes six elements: A - mineral composition of the raw ore, B - weathering degree of the raw ore, C - mineral dissemination state of the raw ore, D - morphological characteristics of the physically separated concentrate, E - SiO2 content of the physically separated concentrate, and F - SiO2 content of the chemically separated concentrate. The rating of each of the six elements includes four levels: a, b, c, and d. The comprehensive rating result provides a quality evaluation of the granite pegmatite-type high-purity quartz raw material. Materials with at least three grades of A are classified as Grade 1 high-purity quartz raw materials; Materials with at least three grades of B or higher are classified as secondary high-purity quartz raw materials; Materials with at least two grades of B or higher are classified as Grade III high-purity quartz raw materials; It is recommended that fewer than two of grade B or higher be developed and utilized as non-high-purity quartz raw materials. The first-grade high-purity quartz raw material can be used to prepare high-purity quartz of grade 4N5 or higher after the purification process is optimized. The secondary high-purity quartz raw material can be used to prepare high-purity quartz of grade 4N or higher after the purification process is optimized. The three-level high-purity quartz raw materials can be used to prepare high-purity quartz of grade 3N or higher after the purification process is optimized.
9. A quality rating system for high-purity quartz raw materials of granite pegmatite type, characterized in that, The quality rating system can realize the quality evaluation method of granite pegmatite-type high-purity quartz raw material as described in any one of claims 1-7, and is based on the quality rating index of granite pegmatite-type high-purity quartz raw material as described in claim 8. The rating system adopts a semi-quantitative threshold grading evaluation method. The evaluation and grading indicators of six elements of granite pegmatite ore and its physical and chemical beneficiation concentrate are programmable through digital signal logic circuits. The rating system is a multi-index rating system composed of a decoder, a full adder, a carry-lookahead adder, a numerical comparator, and a counter. The rating system is configured with six parallel rating modules based on six elements: A, B, C, D, E, and F. Each rating module has four rating indicators: a, b, c, and d. These four rating indicators are represented by two binary numbers A1A0, where a=10, b=01, c=11, and d=00. The rating level of each indicator is input through the binary code A1A0, and after passing through a decoder, a full adder, a carry-lookahead adder, a numerical comparator, and a logic circuit consisting of multiple logic gates connected in series, the system outputs a comprehensive evaluation level of the granite pegmatite raw material: Level 1, Level 2, Level 3, and Level 4. Among them, Level 1 granite pegmatite raw materials can be used to prepare high-purity quartz of grade 4N5 or higher, Level 2 granite pegmatite raw materials can be used to prepare high-purity quartz of grade 4N or higher, Level 3 granite pegmatite raw materials can be used to prepare high-purity quartz of grade 3N or higher, and Level 4 granite pegmatite raw materials are not recommended for development and utilization as high-purity quartz raw materials.
10. The quality rating system for high-purity granite pegmatite-type quartz raw materials according to claim 9, characterized in that, The decoder is a 74LS139 or 74HC139, which can convert two binary A1A0 into one binary number. The full adder adds the binary numbers output by the decoders of the six parallel rating modules, where S is the sum of the bits and C is the carry-in to the higher bits. The carry-lookahead adder is a 74LS283 or a 74HC283, which can add the sum of the two full adders and the carry-in number to calculate the number of ratings a or the number of ratings a+b in the six elements, Na. The numerical comparator is a 74LS85 or 74HC85, which can compare the three-bit sum S2S1S0 output by the adder with (011). B Or (010) B By comparing, we can determine whether Na is not less than 3, Nb is not less than 3, and Nb is not less than 2. Slice 1, Slice 2, and Slice 3 are all modules composed of the carry-lookahead adder and the numerical comparator, which can perform graded counting of the rating indicators of the six elements and compare the corresponding grade numbers at the same time. The first piece is used to calculate the number of a, Na, and then compare Na with (011). B =(3) D For comparison, when Na≥3, the overall grade of the sample is output as Level1; the slice 2 includes calculating the number of a+b (a or b) Na+b and comparing Na+b with (011). B =(3) D For comparison, when Na+b≥3, the overall grade of the sample is output as Level2; the number of a+b (a or b) Na+b in the slice 3 is calculated and Na+b is compared with (010). B =(2) D For comparison, if Na+b≥2, the overall level of the sample is output as Level3; otherwise, the overall level of the sample is output as Level4.